Antimicrobial resistance in bacteria of clinical origin from South African feedlot cattle during 2002-2016 - Naidoo, Vinny (University of Pretoria, 2022)
Mini Dissertation (MSc (Veterinary Industrial Pharmacology))--University of Pretoria, 2020.